Analysis of factors affecting the effectiveness of face-to-face marketing learning via TikTok, YouTube and video conferencing - Eloy Gil-Cordero; Carlos Rodriguez-Rad; Pablo Ledesma-Chaves; María-Elena Sánchez del Río-Vázquez (Heliyon, 2023)
After the COVID-19 pandemic, the use of virtual platforms, social networks and online applications has been totally modified by returning to face-to-face systems. The mandatory use of these tools in the period of social distancing has led to their extensive development. This paper analyzes the effects of the use of ICTs in a purely face-to-face environment. Therefore, it analyzes the factors that affect student satisfaction and effectiveness in marketing learning through the use of digital tools and online applications in face-to-face classes, and this analysis is from a dual perspective of user and learning dissatisfaction. Using a learner-centered approach in university classes, the use of the digital platform Blackboard, the digital tool YouTube and the social network TikTok in university marketing teaching is analyzed. The study is carried out on a sample of 327 university students of different levels. The analysis is performed through a mixed methodology using a symmetric (PLS-SEM) and non-symmetric (fsQCA) approach, allowing a better generalization of the results. In the measurement of effectiveness, both user assessment and student learning assessment are significative, the two being affected in a similar way. However, they are not related to each other, acting independently. Attitude is the construct that has the greatest impact on both types of satisfaction. Perceived enjoyment also exerts a notable influence, especially on learning satisfaction. The study presents one of the first post-pandemic approaches to the analysis of the effectiveness of technological tools (ICT tools) in the face-to-face setting of university marketing classes.